(untitled) (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2026)
This article analyzes the literary, historical, ideological, and artistic significance of Mukhtar Omarkhanovich Auezov’s translation of Leo Tolstoy’s story “Buddha” into the Kazakh language. The study examines the role of the translation in shaping the writer’s creative personality, its connection to his educational and enlightenment-oriented approach, and its influence on the evolution of his humanistic worldview. Furthermore, the article considers the impact of the translation on Kazakh readers and its role in establishing a new cognitive orientation within the national literary space. The analysis highlights the ways in which Tolstoy’s ideas of resistance to violence, spiritual perfection, and the promotion of moral values are conveyed in Auezov’s translation. It identifies the translator’s techniques for aligning the original text with the national cultural code, methods of artistic transformation, and stylistic solutions. Historical-literary, comparative, textological, and interpretative methods are applied, which allows a scholarly justification of Auezov’s translation’s place in Kazakh literature and its significance for the development of spiritual culture. The findings contribute to the advancement of the theory of literary translation, the deepening of Auezov studies and translation studies, enrichment of literature courses at universities, and provide methodological guidance for future research. The material may be useful for humanities researchers, master’s and doctoral students, instructors, literature teachers, as well as a wider audience interested in issues of national spirituality. The conclusions can be applied for academic publications, scientific projects, conference discussions, interdisciplinary studies, and improvement of practical educational processes. Therefore, the article is distinguished by its relevance, fully meets the contemporary requirements of literary scholarship, and is of interest to the scientific community both now and in the future.